Food Allergen Immunotherapy in the Treatment of Patients with IgE-Mediated Food Allergy - Mirjana Turkalj; Adrijana Miletić Gospić; Ivona Višekruna Džidić; Ivana Banić (Medicina, 2024)
The prevalence of allergic diseases, including food allergy, is increasing, especially in developed countries. Implementation of an elimination diet is not a sufficient therapeutic strategy in patients with food allergy, whose quality of life is significantly impaired. In recent years, new effective therapeutic strategies have been developed, such as the application of oral, sublingual, and epicutaneous immunotherapy. Oral immunotherapy is the most often applied strategy because of its effectiveness and ease of application, with an acceptable safety profile. The effectiveness of oral immunotherapy in patients with egg, cow’s milk, and peanut allergy has been proven both in terms of raising of the threshold and the development of tolerance, and in some patients, the development of sustainable unresponsiveness. Although oral immunotherapy is an effective treatment for food allergy, several limitations, including a long duration and a significant rate of reported adverse events, reduces its success. Therefore, new therapeutic options, such as treatment with biologicals, either as combinations with food allergen immunotherapy or as monotherapy with the aim of improving the efficacy and safety of treatment, are being investigated.